TUTURAN MAHASISWA DALAM PRAKTEK PELAYANAN RESTORAN MAHASISWA PROGRAM STUDI DIPLOMA IV PERHOTELAN STIPAR TRIATMA JAYA - Paramita Sari, Ni Luh Komang Julyanti; Prayogi, Putu Agus; Aristana, I Nengah (Akademi Komunitas MAPINDO, 2018)
Bali is always trying to improve itself in aspects of tourism especially in accommodation and services. In terms of service to tourists, communication is one of the most decisive factors. It encourages workers in tourism sector to have good communication skills, especially communication in English. This phenomenon requires the graduates in education and training institutions of hospitality and tourism to have good communication skills, especially communication in English.In this study, researcher raised the students of STIPAR Triatma Jaya joring in Management Business Hospitality as an object of research. The analysis in this study was made to answer the following questions: (1) the problems faced by students in speaking English in terms of speech act (pragmatic), and (2) to find some factors inhibiting students in learning to speak.This researchshowed that students majoring in Management Business Hospitality, experienced problems during the lesson especially in communicate English pronunciation, word selections and the using of English grammar. It is still influenced by the magnitude of the first language or mother tongue. Some factors have limited the students in speaking English, those factors are: components of linguistic mastery, and mastery of the content component, and environmental conditions during the learning process for example, the conditions where there was a little open space in the class room resulting the inclusion of sounds that interfere the process of learning. Keywords:speaking, speect act, barriers, foreign language (English)